Chilocoris serratus n. sp., the first burrower bug species (Hemiptera: Heteroptera: Cydnidae) recorded in Guinea-Bissau with an annotated checklist of the Afrotropical species of the genus Chilocoris Mayr, 1865 - Lis, Jerzy A.; Lis, Barbara (Zootaxa, 2016)
The first burrower bug species recorded in Guinea-Bissau, Chilocoris serratus n. sp., is described and compared with morphologically related species. Additionally, an annotated checklist of Afrotropical species of the genus Chilocoris is provided.